RANCANG BANGUN APLIKASI DEKSTOP UNTUK PENGELOLAAN TAMAN PENDIDIKAN AL-QURâAN - Rofii, Faqih; Mukhsim, Mokh.; Tjahjono, Ngudi; M Mukhtar, Dzurriyat (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2017)
Taman Pendidikan Al-Quran (TPQ) as one of the community-based education requires an effective system and professional in administration and management. Problems that are found relating to the management of TPQ is still manual data management. This paper aims to provide a solution to manage the data that still manual can be completed quickly through a computer application program. The results of the design and implementation of the program is a computer application system that can be operated easily, can be used to manage the data of students, teachers and assets effectively in terms of time and operation, without error or bug, and can present a report of students, assets and financial flows quickly.Â Keywords: TPQ, Computer Application, Data Santri